IMPROPER NUTRITION AND ITS NEGATIVE CONSEQUENCES - Rakhimova Gulshoda Vakhobovna (Scholar Express Journals, 2023)
In the article, the author describes the concept of malnutrition and its possible negative consequences, diseases caused by malnutrition, fast food (he spoke about the dangers of fast food), and also explained the rule of proper nutrition.
Keywords: Improper nutrition; proper nutrition; stomach